Halal Supply Chain Management: A Bibliometric Study - Hanoum, Syarifa; Sugihartanto, Mushonnifun Faiz; Zuhriya, Hana (Halal Research, 2023)
This research aims to provide a literature review using a bibliometric approach to analyze research trends in Halal Supply Chain Management (HSCM). It examines 149 papers from the Scopus and Web of Science databases during 2011-2021. It involves citation and co-citation analysis with the help of VOSviewer software to find out information about research trends, journals, authors, countries, citations, methodology, and the research content. The analysis divides HSCM research into five research clusters: (1) Halal Food Industry; (2) Challenges and Opportunities of Halal Logistics; (3) Integrity Guarantee of Halal Food; (4) Integrity Guarantee of Halal Logistics; (5) Halal Logistics Performance. This study helped to explore halal supply chain management in practice and be useful for researchers and practitioners to know the current development of HSCM research and map the potential topic for future research.